PENGARUH KOMUNIKASI ORGANISASI, MOTIVASI KERJA TERHADAP KINERJA DOSEN PADA UNIVERSITAS NUSA TENGGARA BARAT (UNTB) - yayang erry wulandari (Master of Management, Mataram University, 2017)
This research is aimed at analyzing and determining the significant effect of organizational communication and work motivation on the performance of lecturers in West Nusa Tenggara University (UNTB) Mataram as well as determining which of the variables is the most dominantly affecting the performance of lecturers in West Nusa Tenggara University (UNTB) Mataram. This research is associative or causality study. The respondents were all 59 in this University. The data were analyzed with multiple linear regression using SPSS Program.The research showed that 1) Organisational communication variable had positive and significant effect on the performance of lecturers in West Nusa Tenggara University (UNTB) Mataram, 2) Work Motivation variable had positive and significant effect on the performance of lecturers in West Nusa Tenggara University (UNTB) Mataram, and 3) Organisational Communication variable had the most dominant effect on the performance of lecturers in West Nusa Tenggara University (UNTB) Mataram.Based on these findings, it is recommended that UNTB management improves the level of effective communication and work motivation to improve the level of working performance. It also directs future research to cope with other variables such as the university leaders’ perspectives to triangulate the findings. Keywords : organizational communication, work motivation, performance of lecturers